Post-Secondary Aspirations of High School Seniors from Different Social-Demographic Contexts - O’Neil, G. Patrick (Canadian Journal of Higher Education, 1981)
This study examines post-secondary aspirations of high school seniors from five different residential settings (rural farm, rural nonfarm, village, small-town, and large city) in the Regional Municipality of Durham (Durham Region), Ontario, Canada. A linear regression model sorts out simultaneous effects of the independent variable, residential locale, on the dependent variables, levels of educational and occupational aspiration, with relevant control factors held constant. Results indicate that differences between groups is minimal as residential locale accounts for only a small proportion of the variance in aspirational levels. Nevertheless, as a group, rural nonfarm students have the highest overall levels of post-secondary aspiration, small-town and city students have moderate levels of post- secondary aspiration, and rural farm and village students have the lowest overall levels of post-secondary aspiration. Two variables, in particular, account for most of the variance in the model, namely, parental expectations and peer group. In general, the findings contribute to a better understanding of factors which affect divergent levels of post- secondary aspiration among high school seniors in Durham Region and in areas which approximate Durham Region.